An Overview on the Role of Aflatoxin in the Development of Hepatocellular Carcinoma - Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2024)
In developing countries such as Afghanistan, cancer is the second leading cause of death in humans. Primary liver cancer accounts for approximately 4% of all newly diagnosed cancers worldwide. Around 80% of all liver malignancies globally are hepatocellular carcinomas (HCC). Several factors, including the hepatitis B and C viruses, are involved in the development of liver cancer. In recent years, mycotoxins have contributed to the development of hepatocellular carcinoma in both humans and the majority of domestic and laboratory animals. Among mycotoxins, aflatoxin, and especially aflatoxin B1, is the most well-known carcinogenic agent of hepatocellular carcinoma, classified as group 1 carcinogen by the International Agency for Research on Cancer (IARC). The aim of this review is to look into the carcinogenesis of aflatoxins and how they relate to hepatocellular carcinoma.